Keterjangkauan Perumahan di Indonesia - Rostiana, Endang (Jurnal Trikonomika, 2011)
The major housing problem in Indonesia is provided affordable housing specially for lower income household. Household ability home ownership depends on their housing affordability. This research focuses on measuring housing affordability with three concepts: income affordability, repayment affordability, and residual income affordability. It shows that household with the median income in 33 municipal city of provinces in Indonesia less affordable to purchased house at the median price. Repayment affordability shows that most of household affordable to pay the housing annual mortgage payment, except in the several rural area. The other result shows that the number of household with deficit residual income decrease, but nominal value of deficit increase.